Front Cover: Organosilica Nanoparticles for Gemcitabine Monophosphate Delivery in Cancer Cells (ChemNanoMat 7/2019). Issue 7 (18th June 2019) - Daurat, Morgane; Rahmani, Saher; Bouchal, Roza; Akrout, Alia; Budimir, Jelena; Nguyen, Christophe; Charnay, Clarence; Guari, Yannick; Richeter, Sébastien; Raehm, Laurence; Bettache, Nadir; Gary‐Bobo, Magali; et al.
Abstract : Two kinds of organosilica nanoparticles based on ionosilicas or neutral tertiary amino compounds have been loaded with gemcitabine monophosphate and are able to deliver the drug in cancer cells due to phosphate exchange or pH stimulus. Both nanoparticles are endocytosed in cancer cells, as monitored by fluorescence microscopy, and are very efficient, leading to 60% cancer cell death. These nanoparticles are therefore promising vectors for nanomedicine applications against tumors. More information can be found in the Full Paper by Magali Gary‐Bobo, Jean‐Olivier Durand, Peter Hesemann et al. onpage 888 in Issue 7, 2019 (DOI:10.1002/cnma.201900202 ).